A behaviorista geográfia aktualitása, a kognitív térképezés változó fókuszai = The Current Relevance of Behaviorist Geography: Changing Focuses of Cognitive Mapping - Váncsa, Mariann; Tésits, Róbert (Modern Geográfia, 2024)
This study aims to reveal the change in the research focus of studies related to cognitive mapping from the 1920s to the present day. Another objective of the study is to develop a theoretical framework related to cognitive spatial formation, which builds on secondary literature analysis and the focus areas of mental mapping. It does this in order to designate the structural framework of subsequent subject-specific, primarily EU-related cognitive spatial perception studies. The present investigation is based exclusively on secondary sources, the main aspect of which is the evaluation of behaviorist geography and the emergence of cognitive mapping in international and Hungarian research. In the selection of the literature, an important aspect was the exploration of the focus of research (conceptual and methodological issues) related to subjective spatial perception and its change over time. At the same time, it was important to investigate the role of cognitive mapping in social sciences, with a particular focus on social geography.